Investigating the effect of deictic tracing on multimedia learning. (February 2022) - Schüler, Anne; Wesslein, Ann-Katrin
Abstract: In the reported study it was investigated whether deictic tracing during processing multimedia materials can support learning. Participants in the tracing group had to connect words in the text to corresponding elements in the picture by tracing with their index finger on a tablet surface. Participants in the tracing group were expected to outperform learners in the control group without tracing regarding text-picture integration performance and pure picture recall. Results did not confirm our assumptions. Instead, learners in the tracing group performed even worse regarding text-picture integration performance and drawing performance (i.e., replicating the to-be-learned picture) compared to the control group. Log-file analyses showed that only few learners were able to trace the lines correctly on all slides, so tracing difficulty may explain the unexpected results. Other possible reasons as well as the implications of these results are discussed. Highlights: The effect of deictic tracing on multimedia learning was investigated. A tracing condition was compared to a non-tracing control condition. In the tracing condition, learners connected words to corresponding picture elements. Unexpectedly, tracing let to worse text-picture integration and drawing performance. Log-file analyses showed that learners had difficulty drawing the correct traces.